Livelihood of Former Jute Workers in and around Titagarh Jute Mill Area (International Journal of Scientific Research and Management (IJSRM), 2017)
There is a significant role of jute industry in Indian economy with one of its most important centres in West Bengal, specifically in Hooghly basin. It is given the title of the ‘Golden Fibre’ internationally with its high versatility and cheap price. But unfortunately its market is deterioration with decrease in productivity. Such deterioration has resulted in closing down of various mills stretching its effects on the workers engaged in them. This study deals with the effect on livelihood of former labours of the industry of Titagarh, a major zone concentrating jute mills in north 24 parganas in the left bank of river Hooghly.. The main objectives of the study are to bring out the present scenario of livelihood of former jute workers in and around Titagarh Jute Mill area concentrating in Ward 1, 2 and 3 and illustrate the physical and socio economic attributes that encompasses them. The research is done based on quantitative and qualitative methods based on structured questionnaires on sample size summing up to 150 based on direct interviews with 50 from each ward, and secondary data from various sources. It is found out that the physical setting have provided favourable conditions for settling up of the industry and attracting labours to settle down around it. Unfortunately after closing down of the mills, the conditions of the former workers have deteriorated with dense settlement and lower standard of living which need attention for development. Unfortunately, the deteriorated conditions are intermingled with social unrest and disruptions